EIB Investment Report 2019/2020 - Key Findings accelerating Europe's transformation - European Investment Bank (European Investment Bank, 2019)
The Investment Report, issued annually by the European Investment Bank, provides a comprehensive overview and analysis of investment and the financing of investment in the European Union. It combines the exploration of investment trends with in-depth analysis, focusing especially on the drivers and barriers to investment activity. The report leverages on a unique set of databases and survey data, including EIBIS, an annual survey of 12 500 firms in Europe, which focuses on their assessment of investment and investment finance conditions, and which allows analysis with firm balance sheet information. The report provides critical inputs to policy debates on the need for public action on investment, and on the types of intervention that can have the greatest impact. These key findings, provide a short accessible summary of the main report's messages.